Does belonging to an appellation make a difference? New evidence from Ontario Viticultural Areas - Omer Gokcekus (Wine Economics and Policy, 2021)
Assuming that wine markets are efficient, ultimately a bottle of wine's cost and therefore its price should reflect its vintage, grape variety as well as how it is vinified. Yet, being an experiential good, a wine's price is also closely related to its place of origin. If the designated viticultural area of wine is coming from is not considered, even in a relatively new wine country, wine makers may end up over-estimating the premium attached to vintage, variety as well as how it is vinified. Regression results indicate that, for Ontario wines, the over-estimations vary between 1% points and 18% points.
Keywords: 330; appellation; AVA; price